Analysis of the mechanical properties of banana stem fibers and coconut fibers through tensile strength measurement based on Hooke’s Law - Kurniatillah Kurniatillah; Mawarni Saputri; Elisa Elisa (Universitas Muhammadiyah Mataram, 2026)
The utilization of natural fibers such as banana stem fiber and coconut fiber is still not widespread even though both have good mechanical properties. This study aims to compare the tensile strength of the two types of fibers using the hanging load test method. The study was conducted experimentally at the Physics Education Laboratory of Syiah Kuala University using four specimen groups with 20 samplesin each group (n = 20). The process includes drying the fibers indoors, cutting samples with a size of 20 cm for single fibers and 15 cm for bundles, measuring the diameter using a screw micrometer, and applying a load gradually until the fiber breaks. A total of 80 specimens were tasted using a purposive sampling technique, consisting of sigle banana fibers, sigle coconut fibers, banana fiber bundles, and coconut fiber bundles with relatively similar physical characteristics and diameters. The data obtained were analyzed descriptively using average values of stress, strain, and elastic modulus. The results showed that single coconut fiber had the highest stress of 4.49×10⁶ Pa, an elastic modulus of 2.30×10⁸ Pa, and a strain of 0.0210. Meanwhile, single banana fiber had a stress of 4.34×10⁶ Pa, a modulus of 3.57×10⁸ Pa, and a strain of 0.0017. Coconut fiber bundles showed a stress of 1.76×10⁶ Pa, a modulus of 1.29×10⁸ Pa, and a strain of 0.0145, while banana fiber bundles produced a stress of 1.77 × 10⁶ Pa, a modulus of 6.91 × 10⁸ Pa, and a strain of 0.0033. Coconut fiber was more elastic and less prone to breaking during testing, while banana fiber was stiffer and more prone to breaking. The results of this study concluded that coconut fiber is better suited for applications requiring flexibility, while banana fiber is better suited for applications requiring high stiffness.